2010
DOI: 10.1634/theoncologist.2009-0325
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Limb Perfusion for Malignant Melanoma: Systematic Review on Effectiveness and Safety

Abstract: After completing this course, the reader will be able to:1. Compare the response rate of ILP with melphalan and TNF to the response rate of ILP with single-agent melphalan in patients with unresectable locally advanced melanoma of the limbs.2. Compare the clinical response rates of repeated ILP after a recurrence or PR to a first ILP to clinical response rates after first ILP in patients with unresectable locally advanced melanoma of the limbs.3. In patients with unresectable malignant melanoma of the limbs, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
80
2
21

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 47 publications
(70 reference statements)
11
80
2
21
Order By: Relevance
“…A large systematic review (n=2018 ILPs; 22 trials) found that for patients with unresectable stage IIIB-IIIC metastatic melanoma of the limbs, studies published between 1990 and 2008 reported a median overall response rate of 90% (range, 64%-100%) and a median complete response rate of 58% (range, 25%-89%). 160 Median complete response rate varied somewhat depending on the agents used, ranging from 47% with single-agent melphalan, 45% to 65% for melphalan/actinomycin D combination, and up to 70% with melphalan/TNF-alfa combination. 160 These response rates are mostly derived from retrospective series, and the differences reported depend on definitions of response often spanning decades and on patient selection factors.…”
Section: Regional Therapy: Isolated Limb Perfusion and Infusionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large systematic review (n=2018 ILPs; 22 trials) found that for patients with unresectable stage IIIB-IIIC metastatic melanoma of the limbs, studies published between 1990 and 2008 reported a median overall response rate of 90% (range, 64%-100%) and a median complete response rate of 58% (range, 25%-89%). 160 Median complete response rate varied somewhat depending on the agents used, ranging from 47% with single-agent melphalan, 45% to 65% for melphalan/actinomycin D combination, and up to 70% with melphalan/TNF-alfa combination. 160 These response rates are mostly derived from retrospective series, and the differences reported depend on definitions of response often spanning decades and on patient selection factors.…”
Section: Regional Therapy: Isolated Limb Perfusion and Infusionmentioning
confidence: 99%
“…160 Median complete response rate varied somewhat depending on the agents used, ranging from 47% with single-agent melphalan, 45% to 65% for melphalan/actinomycin D combination, and up to 70% with melphalan/TNF-alfa combination. 160 These response rates are mostly derived from retrospective series, and the differences reported depend on definitions of response often spanning decades and on patient selection factors. The reported differences in response rates may not be clinically significant.…”
Section: Regional Therapy: Isolated Limb Perfusion and Infusionmentioning
confidence: 99%
See 1 more Smart Citation
“…At any rate, it should be considered prior to limb amputation (e.g. because of ulceration of recurrent melanoma) [435,438].…”
Section: Clinical Aspects With Regard To Indicationmentioning
confidence: 99%
“…In a systematic review of 22 studies with 2,018 patients [5], the median complete remission rate (CR) was 58 %, and the response rate (PR + CR) was 90 %; the response rate for melphalan, given as monotherapy, was 46 % and thus lower than when it is used in combination with TNF-a (69 %). Treatment success depends on factors such as tumor stage, the number of in-transit metastases (< 10), and a maximum tumor diameter of < 4 cm [6].…”
Section: Extremity Perfusionmentioning
confidence: 99%